Reaksi Media Peranakan terhadap Perang Tiongkok – Jepang 1937-1939 - Ravando Lie (Universitas Gadjah Mada, 2012)
This research examines the reaction of the Peranakan Chinese in Java to the Sino - Japanese War 1937-1939. The sources used in this research were mostly the newspapers of the Peranakan and the Pribumi. Content analysis was applied as a method to determine the contents in those newspapers, which were relevant to the topic of this research. This study shows that the Peranakan people not only used Sino – Japanese war as their economic vehicle, but also as an effective tool to spread an anti-Japanese propaganda.